(untitled) (Journal of Parents and Teachers, 2017)
The diagnostic evaluation in school often focuses on the quantitative results of the assessment instruments exhibition, when in reality should be the fruit of a process with three stakes: a first phase quantitative taking into account these results, a second phase of criterial character that identifies the underlying processes in the results, and a required third phase of contextualization of the results process that allows us to real feedback from the teaching process and learning.